MODERN PECULIARITIES OF CLINICAL COURSE AND TREATMENT OF RHINOSINUSITIS IN CHILDREN - O.V. Karneeva; T.A. Polunina ("Paediatrician" Publishers LLC, 2009)
The article analyzes modern aspects of therapy in children with acute rhynosinusitis with atypical etiology (Chlamydia pneumoniae, Mycoplasma pneumoniae). Basic medications for the treatment of acute rhynosinusitis caused by atypical agents at the present times are antibiotics from macrolides group. The article reflects effectiveness of antibiotic with wide spectrum azithromycin in treatment of this pathology. Key words: children, acute rhynosinusitis, atypical etiology, treatment. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(4):136-140)